The Influence of Poetic Messages through The Film "Hujan Bulan Juni" by Sapardi Djoko Damono - Nidia Sulistyowati; Marudut Bernadtua Simanjuntak (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2022)
The story is written in the novel and the film “Hujan Bulan Juni” is a literary and language film breakthrough in poetry with the intervention of a culture. This novel was filmed to convey a message from the journey of love that is implied in poetry with a myriad of meanings. The story told tells of two people who have differences in religion, culture, ethnicity, family conflicts, and long-distance relationships are united into a couple that has meaning and meaning, Pingkan who is a Manado girl who becomes a Japanese Literature Lecturer at the University of Indonesia and Sarwono is a Javanese boy who is a Lecturer in Anthropology at the University of Indonesia. The purpose of this study is to analyze the meaning and message implied in the poetry in Pingkan and Sarwono's relationship and analyze cultural interference in their relationship. This film provides meaning regarding the meaning of a relationship struggle. The method used is descriptive, qualitative, and correlational. The results of the study reveal that observing the moral values that can be obtained can provide awareness about differences, struggles, and views about a complicated or complicated conflict.